The Effect of tDCS on EEG Profile During a Semantic Motor Task Divided in a Correct and Incorrect Ways - Caldiroli, Cristina Liviana; Balconi, Michela (Pervasive Computing Paradigms for Mental Health, 2016)
In this experimental we investigated the cortical neuromodulation during a tDCS (transcranial direct current stimulation) section to induce a temporary inhibition of the frontal area. The induced effect of brain modulation was tested on the EEG (electroencephalography) and ERPs (event-related potentials) profile when subjects performed a task in which they had to respond if the object represented in the sequence was correctly or incorrectly used. It was shown that an increased negative peak deflection (N400) is observable in case of semantic anomalies. We attended a significant reduction of this ERPs deflections when tDCS was applied to frontal area. During the detection task, participants were asked to evaluate the semantic correctness of some motor sequences that manipulated simple objects. EEG were registered during the tDCS or no tDCS stimulation. Significant differences between the two conditions and a reduction of the peak amplitude were observed in case of tDCS stimulation.